Podcast solutions : the complete guide to audio and video podcasting - Geoghegan, Michael W. (Michael Woodland), 1968-; Klass, Dan, 1963- (Berkeley, CA : Friends of Ed, 2007)
An updated guide to audio and video podcasting covers such topics as developing a podcast, podcasting equipment and tools, recording a podcast, encoding software, the video and audio editing process, getting listed in podcast directories, the podcast community, and making money with podcasting.
1. Podcasting 101 -- 2. Watching and listening to podcasts -- 3. Podcasting how-to -- 4. Planning your podcast -- 5. Audio podcasting tools -- 6. Recording an audio podcast -- 7. Assembling sound -- 8. Video podcast production -- 9. Preparing your file -- 10. Serving it up -- 11. Getting heard -- 12. Making money with podcasting.
Includes index.
Includes bibliographical references and index.
Keywords: Podcasting; World Wide Web; Broadcasting